178k views
3 votes
What is the result of subtracting in the second equation from the first?

-7x-y=0
7x+8y=-6

User NutCracker
by
5.5k points

1 Answer

6 votes

Answer:


-14x-9y=6

Explanation:

we have


-7x-y=0 ---> First equation


7x+8y=-6 --->Second equation

we know that

To subtract the 2nd equation from the first, negate all three of the second equation terms: -7x-8y=6

and then adds this result with the first equation

so


-7x-y=0\\-7x-8y=6\\--------\\-14x-9y=6

User Fush
by
4.9k points